MANTIQ/LOGIKA SEBAGAI MUQADDIMAH ILMU (KAJIAN TERHADAP PEMIKIRAN AL GHAZALI) - Aziz, Ishak Abd. (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
This article tries to elaborate the position of mantiq /logic in knowledge, especially in Islamic theoretical knowledge or wisdom from al-Ghazali’s point of view based on his book al-Mustafa min ‘Ilm al-Usul (the Quintessence of the Principle of Islamic Jurisprudence). The texts which touch the issue and the brief explanation of mantiq/logical discussion in his book are translated by the writer with anotation and then will be analysed and interpreted objectively.